CONTRIBUTION OF THE PENGGING ISLAMIC’S SOCIETY IN PROMOTING HISTORICAL TOURISM IN THE “TRADISI SEBAR APEM KUKUS KEONG MAS” IN BOYOLALI - Mesrantia Ayunda Putri; Ita Dwijayanti (2024)
Pengging is a heritage/historic area located in Boyolali, Central Java. Some of the historical attractions in Pengging include Umbul Pengging, Cipto Mulyo Mosque, R.Ng's Tomb. Yasadipura, grave of Kyai Ageng Kebo Kenongo (Ki Ageng Pengging). Researchers found that there are many traditions that still survive today, one of the traditions is in Pengging which is carried out every year and was officially declared an Intangible Cultural Heritage by the Ministry of Education and Culture in 2020, namely the Tradition of Spreading the Keong Mas Steamed Apem. The tradition of spreading apem steamed keong mas is an adoption of the Yaqowiyu tradition in Jatinom, Klaten, Central Java. The tradition uses the traditional Gunungan procession, like the tradition at the Surakarta Palace and Yogyakarta Palace. The tradition of spreading apem steamed keong mas is interesting for researchers to study because many of the general public are still not aware of this tradition. This is proven by 30% of Pengging tourist visitors who only visit tourist attractions without knowing about the traditions that are carried out every year. This research uses qualitative historical methods as a research stage carried out using heuristics (data collection by means of interviews with related parties and also collecting sources of oral history of the Pengging community, namely urban legends), verification (critique of sources, this is done by limiting research observations so that the focus is the purpose of this research being carried out), interpretation (analysis carried out by creating a structured narrative whose truth and novelty can be accounted for), and historiography (carried out to convey the results of observations in three chapter discussions which will be completed in approximately 2-6 months). The results of the research focus on the condition of the Pengging community in 2004-2020, an explanation of the Keong Mas Steamed Apem Spread Tradition which is recognized as an Intangible Cultural Heritage by the Ministry of Education and Culture, and the existence of the government in maintaining the Keong Mas Steamed Apem Spread Tradition. As a reference to the Boyolali government not to forget history and raise the historical tourism potential in Pengging. The efforts made by the government to obtain and maintain the existence of recognition as intangible cultural heritage in 2020 during the Covid-19 pandemic have become a challenge for the need for publication/promotion that can be carried out by the government and surrounding millennials.